PENGUJIAN KUALITAS TIGA MEREK DAGANG KAYU LAPIS (PLYWOOD) YANG BEREDAR DI PASARANKOTA BENGKALIS - Okta Faisal; Evi Sri Budiani; M. Mardhiansyah M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Plywood is a composite product made of veneer sheets that are taped together with the arrangement of intersecting perpendicular. This research aims to know the quality of plywood circulating in the market of Bengkalis City based on Indonesian National Standard (SNI 01-5008.2-1999), with various trademarks. Data were analyzed by comparing the results obtained from the measurements with SNI 01-5008.2-1999. The results show the quality of the front and rear layers of three samples included into the Indonesian National Standard, the quality of the layers in the Arwana and Fortune samples are not included in the Indonesian National Standard, the OFR sample is included in the Indonesian National Standard. Testing of plywood moisture content of Arwana sample is not included in Indonesian National Standard, Fortune and OFR samples included into Indonesian National Standard. Testing the development of thickness plywood Arwana, Fortune and OFR samples for 2 and 24 hours included into the Indonesian National Standard. From plywood quality testing conducted OFR samples that meet the Indonesian National Standard. key words : quality, plywood